System Safety Assessment of the Warehouse Operation Using Functional Resonance Analysis Method and Resilience Analysis Grid - Sudiarno, Adithya; Dzaky Ma’arij, Ahmad Murtaja (UI Scholars Hub, 2023)
This study applied the perspective of Safety-II using the Functional Resonance Analysis Method (FRAM) and the Resilience Analysis Grid (RAG) to analyze safety in warehouse operations from a system perspective. FRAM was used to emphasize what caused things to go right, with the findings highlighting higher performance and safety variability occurring in activities that require multiple individual or group efforts. RAG was used to assess the organization’s potentialto handle unexpected occurrences, identify the potential resilience of the warehouse in its daily activities, and evaluate the ability to maintain flow and workersafety based on four pillars of resilience. The assessment resulted in a value of 3.50 in the ability to respond, 2.84 in the ability to monitor, 3.88 in the abilityto learn, and 3.21 in the ability to anticipate. Combining FRAM and RAG enhances the depth of a new perspective of safety analysis and addresses resilience factors in daily operations.